Epigenetics and Female Reproductive Aging - Chamani, Isaac J.; Keefe, David L. (Frontiers in Endocrinology, 2019)
As a result of many social and economic factors, increasing numbers of women are delaying childbirth until a more advanced age [1]. Increasing maternal age has resulted in well documented decreases in fertility [2; 3], and increases in aneuploidy [4], and pregnancy complications [5; 6; 7]. While these risks are clear, the underlying physiological processes that result in these outcomes are much less well defined. Proposed mechanisms involve neuroendocrine deficiency [8; 9], telomere length, meiosis abnormalities [10; 11], mitochondrial dysfunction [12; 13], as well as epigenetic modifications. In this review, we focus on the age- related epigenetic changes that have been found in female reproductive organs, and the effect these changes may contribute to female reproduction.